(untitled) (Ustozlar uchun, 2025)
Goal setting is a fundamental component of personal development and academic achievement. Clearly defined goals help individuals focus their efforts, manage time effectively, and maintain motivation. This article explores the concept of goal setting, emphasizing planning, prioritization, and persistence as the main factors of success. The paper also discusses practical strategies, common challenges, and psychological aspects of goal achievement. By developing effective goal-setting skills, individuals can improve productivity, self-confidence, and long-term success.